Identification and disposition of novel mono‐hydroxyl mefenamic acid and their potentially toxic 1‐O‐acyl‐glucuronides in vivo. (11th August 2015) - Fong, Sophia Yui Kau; Zhang, Yufeng; Wong, Yin Cheong; Zhou, Limin; Han, Quanbin; Zuo, Zhong
Abstract: Mefenamic acid (MEF) is a widely prescribed non‐steroidal anti‐inflammatory drug that has been found associated with rare but severe cases of hepatotoxicity, nephrotoxicity and gastrointestinal toxicity. The formation of protein‐reactive acylating metabolites such as 1‐ O ‐acyl‐MEF glucuronide (MEFG) and 3′‐hydroxymethyl‐MEF 1‐ O ‐acyl‐glucuronide is one proposed cause. In addition to the well‐reported 3′‐hydroxymethyl‐MEF, two mono‐hydroxyl‐MEF (OH‐MEFs) were recently identified in vitro . However, in vivo evidence is lacking and whether these OH‐MEFs would be further glucuronidated to the potentially reactive 1‐ O ‐acyl‐glucuronides (OH‐MEFGs) is unknown. Utilizing UPLC‐Q‐TOF/MS and LC‐MS/MS, the current study identified, for the first time, four OH‐MEFs and their corresponding OH‐MEFGs from plasma after a single oral administration of MEF (40 mg/kg) to rats, including an OH‐MEF that has not been reported previously. The systemic exposure of these identified metabolites was high, with metabolic to parent AUC 0→24h ratios reaching 23–52% (OH‐MEFs) and 8–29% (OH‐MEFGs). These metabolites also had a long systemic exposure time in both single and 5 day multiple oral MEF‐treated rats, with elimination half‐lives between 9 h and > 24 h. In addition to these novel metabolites, the previously reported MEFG was also identified and its systemic exposure was found to be doubled after multiple MEF administrations. These pharmacokinetic results suggest that systemic toxicities caused by the potentially reactive MEFG and OH‐MEFGs could be considerable, especially after repeated MEF treatment. Nevertheless, MEFG and OH‐MEFGs had negligible uptake in the brain, indicating a minimal risk of brain toxicities. Furthermore, an in situ intestinal perfusion study revealed that during MEF absorption, it was extensively metabolized to MEFG while < 5% was metabolized to OH‐MEFs and OH‐MEFGs. Copyright © 2015 John Wiley & Sons, Ltd.